IMPLEMENTASI RENCANA PELAKSANAAN PEMBELAJARAN IPS YANG BERORIENTASI PADA PEMBENTUKAN KARAKTER SISWA DI TINGKAT SMP - Verico Alvian Fernando; Liza Husnita; Zulfa eva (Bakaba, 2018)
Social lesson teachers of junior high school 35 Kerinci made a teaching plan that focus character education, but some of student are not discipline. It mean the teachers are not appropriate with lesson plan that made. They had some problems in teaching procces. The purpose is to describe the implementation of lesson plan that oriented of creating the characterstic of teacher problems. The researcher method use qualitative opproach. The result of the research showed the teachers of junior high school 35 of Kerinci, had some problems with the materials, that they created the lesson plan by copying of internet. The implementation of characters values in teaching procces as implicit not oxplicit, by giving motivation in speech. That made some of students dId not know the characteristic values. It done because the teachers had problems to find RRM valves and success indicator, tools and equipments, and the references used.